Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. V : Michael VIII to Constantine XI, 1258-1453. Pt. 1 : introduction, appendices, and bibliography. - Grierson, Philip. (Washington)
xvi, 285 s.